The Art of Body Contouring - Aguilera, Alexandro (IntechOpen, 2019)
Body contouring surgery is one of the most common procedures performed by plastic surgeons worldwide. New technologies have been developed in all areas of medicine, and aesthetic surgery is no exception. Body contouring surgery is a very passionate field that demands careful planning and flawless execution. This is why we have gathered a group of clinicians and scientists with vast experience in body contouring surgery to discuss breast and body contouring surgery as the main objectives in this book.